Preliminary Phytochemical Analysis and the Anti-Diabetic Effect of Leaf Extracts of Symplocos cochinchinensis (Lour.) Moore ssp. Laurina (Retz.) Nooteb. Against α-Amylase and α-Glucosidase - Trieu Ly, Hai; Le, Vu Khanh Trang (Science & Technology Asia, 2021)
One of the ways of controlling postprandial glucose level is to inhibit carbohydratehydrolyzing enzymes like α-amylase and α-glucosidase. This study was undertaken to provide in vitro evidence for the potential inhibitory activity of crude extract and different fractions of Symplocos cochinchinensis leaves on α-amylase and α-glucosidase enzymes. Crude and fractionated extracts were obtained by percolation and liquid-liquid extraction. In vitro antidiabetic activity of all extracts was assessed based on α-amylase and α-glucosidase inhibition. Furthermore, phytochemical screening was done via chemical reactions, and the total polyphenol (TPC) and flavonoid (TFC) contents were measured via colorimetric methods using S. cochinchinensis leaves. Results showed that S. cochinchinensis leaves contain polyphenols, flavonoids, saponins, triterpenoids, alkaloids, anthraglycosides, anthocyanosides, proanthocyanidins, tannins, polyuronics, and reducing agents. The TPC was 517.71 mg gallic acid equivalent/g dry mass while the TFC was 1.12 mg quercetin equivalent/g dry mass. The results indicated that crude extract and its fractions demonstrated inhibitory activities on both α-amylase and α-glucosidase, of which, the crude extract and ethyl acetate fraction had the highest inhibitory potential for both α-amylase and α-glucosidase of all the fractions tested, with IC50 values of 38.85 and 35.74 μg/mL (crude extract), 30.18 and 30.91 μg/mL (ethyl acetate fraction), respectively. These fractions were especially better than acarbose (45.49 and 53.18 μg/mL). Simultaneously, there was a significant correlation between the TPC of the S. cochinchinensis leaf extracts and their α-amylase and α-glucosidase inhibitory activities. Further in vivo studies should be performed to clarify the regulating effect of S. cochinchinensis leaves on postprandial blood glucose.